One-Pot Synthesis of Zinc-Doped Mesoporous Silica - Hajar Jabkhiro; Mario Luigi Naitana; Eleonora Marconi; Federica Bertelà; Giovanna Iucci; Ilaria Carlomagno; Chiara Battocchio; Carlo Meneghini; Luca Tortora (Crystals)
This paper presents an original method for synthesizing Zn-doped mesoporous silica (KCC-1) via a one-pot microemulsion method followed by hydrothermal treatment. Zn incorporation into the silica matrix was achieved by varying Zn/Si molar ratios from 1% to 8%. The Zn-doping effect on KCC-1 morphological and structural properties was investigated using several characterization techniques, providing new insights into the Zn-doping behavior and coordination environment. X-ray fluorescence (XRF) spectra confirmed the stoichiometric doping of silica nanoparticles for samples obtained with a precursor concentration of 1%, 3%, and 6%. An attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy highlighted that Zn was included into the KCC-1 matrix rather than chemically adsorbed onto the surface. Scanning electron microscopy (SEM) images clearly showed that a low Zn content preserves the KCC-1 fibrous morphology. An X-ray diffraction (XRD) analysis confirmed the amorphous nature of the doped nanoparticles, suggesting a structural disorder of the silica framework at higher Zn concentrations. X-ray photoelectron spectroscopy (XPS) revealed that Zn–(OH)2 bonds increased at a 6% Zn/Si molar ratio, confirming the disordered inclusion of Zn at this doping limit. X-ray absorption near-edge structure (XANES) data revealed that in Zn-doped silica at 3% and 6%, Zn primarily exists in a coordination state similar to zinc-silicates and the amorphous Zn-hydroxyapatite-like phase.